Get Your Facts Right: Preschoolers Systematically Extend Both Object Names and Category-Relevant Facts - Holland, Amanda K.; Mather, Emily; Simpson, Andrew; Riggs, Kevin J. (Frontiers in Psychology, 2016)
There is an ongoing debate over the extent to which language development shares common processing mechanisms with other domains of learning. It is well-established that toddlers will systematically extend object labels to similarly-shaped category exemplars (e.g., Landau, Smith, & Jones, 1988; Markman & Hutchinson, 1984). However, previous research is inconclusive as to whether young children will similarly extend factual information about an object to other category members. We explicitly contrast facts varying in category relevance, and test for extension using two different tasks. Three- to four-year-olds (N = 61) were provided with one of three types of information about a single novel object: a category-relevant fact (‘it’s from a place called Modi’), a category-irrelevant fact (‘my uncle gave it to me’), or an object label (‘it’s called a Modi’). At test, children provided with the object name or category-relevant fact were significantly more likely to display systematic category extension than children who learnt the category-irrelevant fact. Our findings contribute to a growing body of evidence that the mechanisms responsible for word learning may be domain-general in nature.